2020
DOI: 10.1111/famp.12611
|View full text |Cite
|
Sign up to set email alerts
|

Mastery and Marital Processes: Mechanisms Linking Midlife Economic Adversity and Later‐Life Loneliness for Husbands and Wives in Enduring Marriages

Abstract: Research has documented that loneliness is a major public health concern, particularly for older adults in the United States. However, previous studies have not elucidated the mechanisms that connect family economic adversity to husbands’ and wives’ loneliness in later adulthood. Thus, using prospective dyadic data over 27 years from 254 enduring couples, the present study investigated how spouses’ mastery, as an intraindividual process, and marital functioning, as a couple process, link midlife family economi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…Furthermore, the life course stress process perspective posits that 'the hardships and stressors most inimical to mastery are, first, those that are stubbornly persistent despite efforts to avoid or ameliorate them; and, second, those that are located within the most salient areas of life' (Pearlin et al, 2007, p. 166). Consequently, because financial problems are highly salient for middle-aged parents, and these problems often continue over an extended period of time, both husbands' and wives' FFS is expected to be strongly associated with a decline in sense of control during the middle years (Lachman & Weaver, 1998;Wickrama & O'Neal, 2020). Depletion of husbands' and wives' sense of control may be attributed to several psycho-social mechanism.…”
Section: Financial Stress and Sense Of Control In Middle Yearsmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the life course stress process perspective posits that 'the hardships and stressors most inimical to mastery are, first, those that are stubbornly persistent despite efforts to avoid or ameliorate them; and, second, those that are located within the most salient areas of life' (Pearlin et al, 2007, p. 166). Consequently, because financial problems are highly salient for middle-aged parents, and these problems often continue over an extended period of time, both husbands' and wives' FFS is expected to be strongly associated with a decline in sense of control during the middle years (Lachman & Weaver, 1998;Wickrama & O'Neal, 2020). Depletion of husbands' and wives' sense of control may be attributed to several psycho-social mechanism.…”
Section: Financial Stress and Sense Of Control In Middle Yearsmentioning
confidence: 99%
“…As depicted in Figure 1, drawing from the life course stress process perspective (Pearlin et al., 2005; Turner, 2010), we expect that the long‐term FFS‐pain association may partly operate through the depletion of individuals' sense of control or mastery. Sense of control has increasingly been recognized as an important psychological resource that is associated with behavioural and health outcomes (Pressman & Cohen, 2005; Wickrama & O'Neal, 2020). Indeed, a number of studies suggest that individual psychological resources, including sense of control, consist of two distinct components.…”
Section: The Theoretical Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, research has shown that persistent family financial stress depletes individuals' resources, including their sense of self-worth and mastery (Pearlin et al, 2007). Recent studies have shown that the depletion of these resources contributes to experiences of bodily pain (Chou et al, 2016) and loneliness in later years (Wickrama & O'Neal, 2020).…”
Section: Family Financial Stress and Health Outcomesmentioning
confidence: 99%